Factors Affecting Cybersecurity Behaviour in the Metaverse: A Hybrid SEM-ANN Approach Based on Deep Learning - ALMANSOORI, AFRAH (2023)
Cybersecurity procedures and policies are prevalent countermeasures for protecting organizations from cybercrimes and security incidents. However, without considering human behaviours, implementing these countermeasures will remain useless. Cybersecurity behaviour has gained much attention in recent years. However, little is known concerning the factors that influence the cybersecurity behaviour of Metaverse users. Consequently, this research has three key objectives. A comprehensive systematic review is steered to address research gaps in the current literature on cybersecurity behaviour via the lens of information system models and theories to identify the most prevalent factors, theoretical models, technologies and services, and participants. The systematic review identified 2,210 empirical studies published on cybersecurity behaviour between 2012 and 2021. In line with the existing gaps found in the literature, this research, therefore, develops an integrated model based on extracting constructs from the Protection Motivation Theory (PMT), Health Belief Model (HBM), and Theory of Interpersonal Behaviour (TIB). An external factor, “trust”, is also incorporated in the model to understand better the factors affecting the cybersecurity behaviour in the Metaverse. The developed model was then evaluated based on survey responses from 531 Metaverse users in the United Arab Emirates who used the Metaverse for personal or professional purposes. The empirical data were analysed using a deep learning-based hybrid Structural Equation Modeling (SEM) and Artificial Neural Network (ANN) Approach. The integrated model explained 66.1% of the total variance in cybersecurity behaviour. The hypotheses testing results reinforced most of the suggested hypotheses in the developed model. The sensitivity analysis results for the ANN model revealed that “cues to action” have the most considerable importance in understanding cybersecurity behaviour in the Metaverse, with 97.8% normalized importance, followed by habit (69.7%), perceived vulnerability (69.6%), self-efficacy (40.9%), and trust (27.2%). Theoretically, integrating the PMT, HBM, and TIB along with the external factor, “trust”, is believed to add a significant value to validating the three theories in general and the cybersecurity behaviour in specific. Practically, understanding the impact of security factors would assist in understanding the effect of security incidents on cybersecurity behaviour in the Metaverse. Furthermore, policymakers and regulators should pay attention to and analyse the present data privacy policies and legislation to create specific policies and regulations for using the Metaverse. Moreover, cybersecurity companies, system analysts, and developers can use the insights from the essential factors as a form of a lesson to the refinement of presently implemented solutions as well as the anticipation of new future technological advancements.